Capital inflows and euro area long-term interest rates - Daniel Carvalho; Michael Fidora (European Central Bank (ECB), 2015)
Capital flows into the euro area were particularly large in the mid-2000s and the share of foreign holdings of euro area securities increased substantially between the introduction of the euro and the outbreak of the global financial crisis. We show that the increase in foreign holdings of euro area bonds in this period is associated with a reduction of euro area long-term interest rates by about 1.55 percentage points, which is in line with previous studies that document a similar impact of foreign bond buying on US Treasury yields. These results are relevant both from a euro area and a global perspective, as they show that the phenomenon of lower long-term interest rates due to foreign bond buying is not exclusive to the United States and foreign inflows into euro area debt securities may have added to increased risk appetite and hunt-for-yield at the global level.
Keywords: E43; E44; F21; F41; G15; 330; capital flows; long-term interest rates ECB